2017
DOI: 10.1002/stem.2635
|View full text |Cite
|
Sign up to set email alerts
|

CD36 Is a Marker of Human Adipocyte Progenitors with Pronounced Adipogenic and Triglyceride Accumulation Potential

Abstract: White adipose tissue (WAT) expands in part through adipogenesis, a process involving fat cell generation and fatty acid (FA) storage into triglycerides (TGs). Several findings suggest that inter-individual and regional variations in adipogenesis are linked to metabolic complications. We aimed to identify cellular markers that define human adipocyte progenitors (APs) with pronounced adipogenic/TG storage ability. Using an unbiased single cell screen of passaged human adipose-derived stromal cells (hADSCs), we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 53 publications
2
67
0
1
Order By: Relevance
“…Accordingly, proliferation rates of murine fibroblasts are not only determined by their age and fibroblast lineage identity but also by the dermal composition (Lichtenberger et al, 2016).Thus, functional heterogeneity of distinct fibroblast subsets is defined by both their identity and microenvironment. For example, CD36 expression is higher in the lower dermis where adipogenesis occurs, which is coherent with its reported function (Gao et al, 2017a(Gao et al, , 2017b. Dermal microvascular endothelial cells also display heterogeneous CD36 expression depending on their localization within the dermis (Petzelbauer et al, 1993).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Accordingly, proliferation rates of murine fibroblasts are not only determined by their age and fibroblast lineage identity but also by the dermal composition (Lichtenberger et al, 2016).Thus, functional heterogeneity of distinct fibroblast subsets is defined by both their identity and microenvironment. For example, CD36 expression is higher in the lower dermis where adipogenesis occurs, which is coherent with its reported function (Gao et al, 2017a(Gao et al, , 2017b. Dermal microvascular endothelial cells also display heterogeneous CD36 expression depending on their localization within the dermis (Petzelbauer et al, 1993).…”
Section: Discussionmentioning
confidence: 61%
“…FAP þ CD90 þ also expressed high levels of COL11A1 and FMO1 (Figure 2e, and see Supplementary Figure S1g). Both FAP e CD90 þ and FAP þ CD90 þ fibroblasts displayed high expression levels of CD36 and PPARg, both of which are involved in fatty acid metabolism and adipogenesis (Gao et al, 2017a(Gao et al, , 2017bSiersbaek et al, 2010). These findings indicate that while FAP þ CD90 e cells represent papillary fibroblasts, FAP e CD90 þ cells depict reticular fibroblasts.…”
Section: Isolation Of Functionally Distinct Papillary and Reticular Fmentioning
confidence: 89%
“…down the osteogenic and chondrogenic mesenchymal lineages) or indeed their therapeutic potential, remains to be explored. CD271 expression has previously been associated with enhanced activity in ASC differentiation assays (Quirici et al, 2010;Barilani et al, 2018;Kohli et al, 2019) and CD36 has been associated with enhanced adipogenic potential (Gao et al, 2017). However, to our knowledge expression of podoplanin, a marker that is used to define lymphatic endothelial cells, has not been reported previously on human uncultured, ex vivo ASC.…”
Section: Discussionmentioning
confidence: 87%
“…While much attention has been paid to identifying differences between white, brown, and brite/beige adipocytes, there is growing evidence that there is functional heterogeneity among white adipocytes themselves. Thus, studies have shown that individual white adipocytes within a single depot may differ in insulin-stimulated glucose uptake, maximal lipogenic rate, response to catecholamines, and uptake of free fatty acids (Salans & Dougherty, 1971;Gliemann & Vinten, 1974;Seydoux et al, 1996;Varlamov et al, 2015;Gao et al, 2017). Indeed, lineage tracing analyses have begun to uncover the differential developmental origins of adipocytes even within single fat depots (Chau et al, 2014;Sanchez-Gurmaches & Guertin, 2014).…”
Section: Introductionmentioning
confidence: 99%